Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The role of the hidden curriculum in enhancing intellectual security in Saudi education from the point of view of students of the third secondary students and the reasons for its weakness from the point of view of teachersMrs. Nouf Atallah Al-Enezi , Mrs. Sarah Mohammed Al-Rashidi , Mrs. Ataf Lahiq Al-Anzi2. The effect of the using Prior & Acquired Knowledge Strategy on Achievement in Science and Reflective Thinking among Seventh Graders in UNRWA SchoolMrs. Eman Ahmad Ayesh3. Trends of middle school students in Al-Ahsa Governorate in the use of simulation technology in educationMr. Ahmed Sami Al-Nasser , Prof. Ahmed Abdullah Al-Dariwish4. The Impact of the Implementation of Comprehensive Quality Assurance Standards on Achieving Modern Global Trends in Teaching Science to Public Secondary School Students in KhartoumDr. Taghreed Mohamed Osman Mahmoud Yousif5. The Degree of Mathematics Teachers' Use of Electronic Assessment Tools in the Primary Stage from their Perspective and Educational Supervisors' Perspective in Makkah regionMr. Hani Talal Ayesh Al-Lahyani6. Psychological happiness among workers and volunteers at the COVID-19 Vaccine Center in Taif GovernorateAsst-Prof. Jaza Obeid Alosaimi, Co-Prof. Asmaa Abdulaziz Al-Hussein7. Evidence-Based Practices for early childhood teachers for deaf and hard of hearing According to the Council for Exceptional Children Standards (CEC)Mrs. Nouf Ali Alghamdi , Dr. Mazen Abdulrahman Alghamdi8. The Quality of Work Life and the Relationship Motivation for Achievement of Faculty Members Hail University in the Kingdom of Saudi ArabiaAsst-Prof. Jaza Obeid Alosaimi , Asst-Prof. Ayesha Alnemah Alaghdaf
Keywords: Journal of Educational and Psychological Sciences